2018
DOI: 10.1177/1849543518805355
|View full text |Cite
|
Sign up to set email alerts
|

Smart niosomes of temozolomide for enhancement of brain targeting

Abstract: Drug delivery to the brain is challenging because of the low permeability of blood–brain barrier, and therefore, optimum concentration of chemotherapeutics in the target area specifically for glioblastoma, an aggressive brain tumor, opens a new path of research. To achieve the goal, the oral alkylating agent temozolomide was incorporated into niosomes, and the surface was modified with chlorotoxin, a small 36 amino acid peptide discovered from the venom of scorpion Leiurus quinquestriatus. Active targeting usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 33 publications
(41 reference statements)
0
30
0
Order By: Relevance
“…It has been shown that surface modification of the niosomes promotes the target specificity for the cancer drug delivery system. For instance, modification of temozolomide-loaded niosomes with chlorotoxin, a target-specific peptide, significantly enhanced the gliomas targeting efficiency of the temozolomide [59]. A study reported that surface modified niosomes containing olanzapine (an atypical antipsychotic drug) showed a 3-fold increase in olanzapine concentration in the brain compared to the intranasal solution of the drug [60].…”
Section: Niosomesmentioning
confidence: 99%
“…It has been shown that surface modification of the niosomes promotes the target specificity for the cancer drug delivery system. For instance, modification of temozolomide-loaded niosomes with chlorotoxin, a target-specific peptide, significantly enhanced the gliomas targeting efficiency of the temozolomide [59]. A study reported that surface modified niosomes containing olanzapine (an atypical antipsychotic drug) showed a 3-fold increase in olanzapine concentration in the brain compared to the intranasal solution of the drug [60].…”
Section: Niosomesmentioning
confidence: 99%
“…In addition, drug delivery systems enhance the radiation effect of radioisotopes due to distance between radioisotope and NPs. Gholami et al showed the effect of Feraheme Ò NPs on the radiation damage of different types of radioisotopes, including 213 Bi, 223 Ra, 90 Y, 177 Lu, and 67 Cu by the use of computational modeling. They demonstrated not only radio-enhancement for internal RT by use of NPs, but also the strongest interaction with 20 nm inter-NP distance.…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…11 In addition, SIR-Spheres Ò , 90 Y-labeled resin microspheres, are approved by FDA for the treatment of unresectable hepatocellular carcinoma. 12 Zevalin Ò , 90 Y-labeled form of ibritumomab tiuxetan, and Bexxar Ò , 131 I-labeled form of tositumomab, are used for the treatment of lymphoma. 13 These b --emitting radiopharmaceuticals are not commonly applied to the patients because of economic and logistic problems.…”
Section: Introductionmentioning
confidence: 99%
“…Among various techniques of niosomal formation, thin-film hydration technique is widely used because it is simpler than the others. The examples of success studies by using the technique are the niosomes entrapped with temozolomide 22 , etoricoxib 23 , stavudine 24 , cefixime 25 , and piroxicam 26 . However, niosomes formed by the technique are multi-lamellar vesicles (MLVs) 27,28 .…”
Section: Fig 1: Distribution Of Particle Sizes Of Each Niosome Formumentioning
confidence: 99%